A New Formation Mechanism of Counterstreaming Mass Flows in Filaments and the Doppler Bullseye Pattern in Prominences - Chengrui Zhou; Yuandeng Shen; Chun Xia; Dongxu Liu; Zehao Tang; Surui Yao (The Astrophysical Journal, 2025)
The eruption of a solar prominence can eject substantial mass and magnetic field into interplanetary space and cause geomagnetic storms. However, various questions about prominences and their eruption mechanism remain unclear. In particular, what causes the intriguing Doppler bullseye pattern in prominences has not yet been solved, despite some preliminary studies proposing that they are probably associated with counterstreaming mass flows. Previous studies are mainly based on single-angle and short-timescale observations, making it difficult to determine the physical origin of Doppler bullseye patterns in prominences. Here, taking advantage of stereoscopic observations taken by the Solar Dynamics Observatory and the Solar Terrestrial Relations Observatory and a three-dimensional numerical simulation, we investigate the origin of the prominence Doppler bullseye pattern by tracing a long-lived transequatorial filament/prominence from 2012 July 23 to August 4. We find that the Doppler bullseye pattern can be launched by repeated coronal jets at one end of the prominence. It is evidenced in our observations and simulation that during the forward traveling of jet plasma along the helical magnetic field structure of the prominence, part of the ejecting plasma can not pass through the apex of the prominence due to the insufficient kinetic energy and therefore forms a backward-moving mass flow along the same or neighboring magnetic field lines. This process finally forms counterstreaming mass flows in on-disk filaments. When the on-disk filament rotates to the solar limb to be a prominence, the counterstreaming mass flows are naturally observed as a Doppler bullseye pattern.